THE ASSESSMENT OF EMPLOYEE RIGHTS AND OBLIGATIONS FROM ISLAMIC PERSPECTIVE ON EXPEDITION COMPANIES IN SURABAYA - Aisyah Ayuningtyas; Eko Fajar Cahyono (Universitas Airlangga, 2020)
This study aims to determine the assessment of the rights and obligations of workers from the Islamic economic perspective. Employee rights comprise wages, suitability of workers with work, Life insurance, Pension funds, Almsgiving entrepreneurs, Accident insurance, Expedition services, proper treatment from colleagues and vehicle facilities from the company. While employee obligations consist of having a sense of sincerity and enthusiasm and having a good religious nature. Case study on employees of the expedition member company ALFI (Indonesian logistics and forwarder association) in Tanjung Perak Port Surabaya. This study uses a quantitative descriptive approach with simple tabulations. The retrieval of primary data in this study was conducted using a questionnaire. The sample in this study were 202 employees of ALFI. This study found that the respondents considered agreeing on the indicators of employee rights such as wages, suitability of workers with work, life insurance, charity of employers and were treated well by colleagues and employers. The respondents also chose to disagree with the rights indicators such as pension funds, accident insurance, expedition services and vehicle facilities from the company. On the indicators of employee obligations, the respondents chose to agree on all indicators which included having a sense of sincerity and enthusiasm and having a good religious character.Keywords: Islamic Employment, Employee Rights and Obligations of employees.REFFERENCE Afzalur Rahman. (1995). Doktrin ekonomi Islam Jilid I, Yogyakarta: Dana Bhakti Wakaf.Badan Pusat Statistik (BPS) Surabaya Jawa Timur. (2014). Indikator tenaga kerja kota Surabaya. Dewan Pengurus Nasional FORDEBI & ADESI Ekonomi dan Bisnis Islam. (2017). Seri konsep dan aplikasi ekonomi dan bisnis Islam.Payaman J Simanjuntak. (1998). Pengantar ekonomi sumber daya manusia, Ed. 2. LPFEUI: Jakarta.Pemerintah Indonesia. (2003). Undang Undang no 13 tahun 2003 yang mengatur tentang ketenagakerjaan. Lembaran Negara RI tahun 2003, No. 13.Sekretariat Negara. Jakarta.Pius Partanto, dkk. (2001). Kamus ilmiah popular. Surabaya: Arkola.H.A. Mu’thi Nurdin. (Tanpa Tahun). Masyarakat Islam, Cet. II. Bandung: Yayasan at-Taufik dan PT. Al Ma’arif.Syarif Chaudhry, Muhammad. (2012). Sistem ekonomi islam prinsip dasar. Jakarta: kencana